2012
DOI: 10.1097/jcn.0b013e318239f5f5
|View full text |Cite
|
Sign up to set email alerts
|

Patient Recovery and Transitions After Hospitalization for Acute Cardiac Events

Abstract: Despite increased attention to providing seamless transitions after hospitalization, patients often feel unprepared, lack knowledge, and may be confused by what to expect during recovery at home after a cardiac event. Care transition after hospital discharge could be improved by informing and counseling patients more specifically about expected recovery after a cardiac event. Therefore, an integrative review of research was conducted to evaluate cardiac patients' trajectory of recovery after hospitalization. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 86 publications
1
32
0
1
Order By: Relevance
“…The findings of this secondary data analysis add support to existing evidence that patients experience ongoing symptoms after an ED visit for potential ACS (Barnason et al, 2012). The analysis also reveals that individuals vary in both their initial symptom severity and rate and direction of change—a finding that has not been previously described in this population.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The findings of this secondary data analysis add support to existing evidence that patients experience ongoing symptoms after an ED visit for potential ACS (Barnason et al, 2012). The analysis also reveals that individuals vary in both their initial symptom severity and rate and direction of change—a finding that has not been previously described in this population.…”
Section: Discussionsupporting
confidence: 77%
“…This timeframe was chosen because a significant portion of patients are readmitted within 30 days after discharge, and many report symptoms up to six months later (Barnason, Zimmerman, Nieveen, Schulz, & Young, 2012; Vashi et al, 2013). The goals of this exploratory investigation were to increase understanding of these symptom trajectories, generate further testable hypotheses, and inform education for patients and healthcare providers about symptom trajectories after hospital discharge.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…14,18 Development of the interview guide was guided by Haggerty et al’s 6 definition of continuity of care (Box 1). The interview guide was slightly modified after performing two pilot interviews.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Furthermore, these studies showed that patients experienced negative relationships with healthcare providers, poor communication and difficulties in progressing through the system, and that they received insufficient information about further policy and follow-up appointments. 9,1115 It seems that the first weeks after discharge are difficult for patients, and it is important that care is coherent and consistent with their medical and psychosocial needs. 5,16 Few studies have analysed patients’ experiences of continuity of care in a comprehensive manner, and they typically have focused on only one type of continuity or one care level.…”
Section: Introductionmentioning
confidence: 99%